Technology Factors Dan Pengaruhnya Terhadap Knowledge Sharing Dan Firm Innovation Capability Pada UKM Bordir Pasuruan - Maulidia (Journal of Economic, Management and Entrepreneurship, 2023)
This study analyzes the effect of Technology Factors on Knowledge Sharing and Firm Innovation Capability. The object of this study is the owner of SMEs Bordir in the District of Bangil Pasuruan. This research is an explanatory research with a quantitative approach. Exogenous variables used are technology factors and endogenous variables used are knowledge sharing and firm innovation capability. The population in this study is the owner of SMEs Bordir in Bangil District. Questionnaires were distributed to 230 SMEs using the Simple Random Sampling technique. This research uses Path Analysis. The results of this study stated that 1) Technology Factors proved to have a significant effect on the Knowledge Sharing variable. This means that the existence of Technology Factors provided by SMEs can help employees in the Knowledge Sharing process. 2) Technology Factors are proven to have a significant influence on the Firm Innovation Capability variable. This means that with the existence of well-managed Technology Factors can help SMEs to find differentiating competencies that enable SMEs to produce better products than their competitors. 3) Knowledge Sharing is proven to have a significant effect on Firm Innovation Capability. This means that the higher the level of Knowledge Sharing that exists in every SMEs, the higher the opportunity for SMEs to innovate